The effect of capital structure on firm's profitability performance: evidence property firms listed in Bursa Malaysia / Mutiara Atiqah Mardhiyyah Khalid - Khalid, Mutiara Atiqah Mardhiyyah (2017)
In recent years, investors have increased their ownership in Malaysian listed firms. As for period January 2007 to December 2016 for listed property firms in Bursa Malaysia, as we can see Malaysia’s current situation of the economy crisis are not certain where it may change the interest rate of the treasury bills for the firms. The main objective is to investigate which one of debt, leverage risk, interest rate, and debt to equity can give effect to capital structure on the profitability of firm’s performance. Based on robust test results, that interest rate is significant negative relationship with firm’s performance where as for every 1% increase in interest rate, return on equity will decrease by 193.66%. It shows that if the economy become in worst situation condition which the interest rate will increase, properties firm’s performance will become in worst result when in year of economic crisis happen. As the recommendation, a firm should monitor all of the decision that taken for each of the strategies so that it will gain the firm’s profitability and the investors of the firms will stay and become increase as they trust on how the managers manage the firm.